Pre-breeding assessment of Macedonian wheat germplasm diversity and yielding potential - Ivanovska, Sonja; Jankulovska, Mirjana; Boshev, Dane; Sandeva Atanasova, Nadica (Macedonian Journal of Ecology and Environment, 2023)
A wheat breeding program in North Macedonia resulted in a large collection of germplasm. In order to increase the efficiency of using genetic variation within this germplasm, the potential breeding value of 217 genotypes was evaluated through the following traits: duration of heading, flowering, and maturity, plant height, spike length, number of spikelets per spike, number of kernels per spike, and thousand kernel weight. The experiment was carried out in 2016, at two locations (Skopje and Gradsko) with different climatic conditions. Duration of phenophases was similar in both locations, indicating satisfactory adaptability of the genotypes to different environments. The average values of the productive traits were higher in Skopje, compared to Gradsko, which was expected considering that Gradsko is located in an arid region. Drought conditions predominantly affected the thousand kernel weight, number of kernels per spike, and plant height, as the average values for these traits were 23%, 16%, and 8% (respectively) lower compared to the average values in Skopje. However, some genotypes have shown greater adaptability to both locations and stable productive traits, representing valuable breeding material in order to improve the wheat’s potential to resist drought and harsh growth conditions. Except for the differences among the average values, wide ranges of the values on the level of genotypes indicated broad diversity within the germplasm. According to the Principal component analysis, genotypes were separated into five different groups, while the cluster analysis confirmed wide genetic diversity among the germplasm, resulting in five distinct clusters, each containing many sub-clusters. The genotypes with high values for the number of spikelets per spike, number of kernels per spike, and thousand kernel weight and low values for plant height, separated into group 4 can be used for improving wheat yield potential, as these traits are positively correlated with seed yield.